Manufacturing method and manufacturing equipment for membrane-electrode assembly

By applying liquid on the surface of the catalytic layer and performing hot pressing treatment, the problems of adhesive strength and production efficiency of the membrane electrode joint are solved, and efficient manufacturing of membrane electrode joints is achieved, avoiding the problems of degradation of battery performance and low production efficiency.

JP7626064B2Active Publication Date: 2025-02-04TORAY INDUSTRIES INC
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2021512599
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-12-23
Filing Date
2020-12-21
Publication Date
2025-02-04
Estimated Expiration
2040-12-21

AI Technical Summary

Technical Problem

In the prior art, when manufacturing the film electrode joint, it is difficult to improve production efficiency while ensuring the bonding strength, and there are problems such as increasing resistance and degradation of battery performance.

Method used

The method of hot pressing is adopted to apply liquid on the surface of the catalytic layer. By evaporating and vacuuming of the liquid during the hot pressing process, the bonding strength between the catalytic layer and the electrolyte membrane is improved while maintaining high production efficiency.

Benefits of technology

The adhesive strength between the catalytic layer and the electrolyte membrane is improved under low pressure and low temperature conditions, avoiding the problems of degradation of battery performance and low production efficiency, and improving the quality and production efficiency of the membrane electrode joint.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007626064000004
    Figure 0007626064000004
  • Figure 0007626064000005
    Figure 0007626064000005
  • Figure 0007626064000006
    Figure 0007626064000006
Patent Text Reader

Abstract

A method for producing a membrane electrode assembly, in which a gas diffusion layer with a catalyst layer is bonded to an electrolyte membrane, said method comprising a liquid application step wherein a liquid is applied only to the surface of the catalyst layer before bonding in the ambient atmosphere, and a thermocompression bonding step wherein the electrolyte membrane and the gas diffusion layer with the catalyst layer to which the liquid has been applied are bonded to each other by means of thermocompression. Consequently, the present invention provides a production method that is capable of achieving a good balance between relaxation of the conditions for thermocompression bonding and improvement of the adhesion between an electrolyte membrane and a gas diffusion layer with a catalyst layer, with high productivity, during the production of a membrane electrode assembly in which a polymer electrolyte membrane and a gas diffusion layer with a catalyst layer are bonded to each other. 
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method and an apparatus for producing a "membrane-electrode assembly," which is one embodiment of a membrane-catalyst assembly, that is, a component formed by bonding a polymer electrolyte membrane and a catalyst layer and used in electrochemical devices such as solid polymer fuel cells. [Background technology]

[0002] Fuel cells are a type of power generation device that extracts electrical energy by electrochemically oxidizing fuels such as hydrogen and methanol, and have been attracting attention in recent years as a clean energy supply source. Among them, solid polymer fuel cells have a low standard operating temperature of around 100°C and a high energy density, and are therefore expected to be used in a wide range of applications as power generation devices for relatively small-scale distributed power generation facilities and mobile vehicles such as automobiles and ships. The polymer electrolyte membrane (hereinafter sometimes simply referred to as the "electrolyte membrane") is the key material of solid polymer fuel cells, and in recent years, further research has been conducted into their application to hydrogen infrastructure-related equipment such as solid polymer electrolyte membrane water electrolysis devices and electrochemical hydrogen pumps.

[0003] When applying polymer electrolyte membranes to such electrochemical devices, components that combine the electrolyte membrane and a catalyst layer are used. A representative example of such a component is a membrane electrode assembly (MEA), which has a gas diffusion layer with a catalyst layer formed on the surface of an electrolyte membrane.

[0004] The following method is known as a method for manufacturing an MEA. First, a sheet called a gas diffusion layer, which is made of gas-permeable carbon paper or the like, is used as a substrate, and a catalyst solution is applied to the surface of the sheet. Then, the solvent in the applied catalyst solution is evaporated to form a dried catalyst layer-attached gas diffusion layer. Furthermore, the dried catalyst layer-attached gas diffusion layer and the electrolyte membrane are thermocompression-bonded using a surface press or roll press to bond the catalyst layer-attached gas diffusion layer to the polymer electrolyte membrane. The reason for adopting the method of bonding the catalyst layer to the electrolyte membrane after drying it in this way is that if the solvent in the catalyst solution adheres to the electrolyte membrane, the electrolyte membrane will swell, wrinkle, and lose its shape.

[0005] However, when a dry catalyst-layered gas diffusion layer is thermocompressed to an electrolyte membrane, the adhesion between the catalyst layer and the electrolyte membrane may be insufficient unless the layer is pressed at high temperature and pressure for a long time. On the other hand, if harsh thermocompression conditions are applied to improve the adhesion between the catalyst layer and the electrolyte membrane, the catalyst layer may be compressed and deformed, resulting in a decrease in gas diffusivity and a failure to obtain good power generation performance, or the electrolyte membrane may be damaged by thermal stress and its durability may be reduced, and the gas diffusion layer may be compressed and deformed, resulting in a decrease in gas diffusivity or even damage. On the other hand, simply lowering the temperature and pressure of the press to reduce damage to the catalyst-layered gas diffusion layer and the electrolyte membrane requires an increased pressing time, which significantly reduces productivity.

[0006] Therefore, various techniques have been proposed to realize good adhesion between the electrolyte membrane and the catalyst layer while mitigating the thermocompression bonding conditions. [Prior art documents] [Patent documents]

[0007] For example, proposed methods include a method in which a catalyst solution is semi-dried and a small amount of solvent component remains in the catalyst layer before bonding it to an electrolyte membrane (Patent Document 1); a method in which a solution containing a binder resin having proton conductivity is applied to the surface of a dried catalyst layer and then the catalyst layer is bonded to the electrolyte membrane before the solution is completely dried (Patent Document 2); and a method in which a laminate including an electrolyte membrane and a catalyst layer is pressure-bonded while immersed in a liquid (Patent Document 3). [Patent Document 1] Patent No. 4240272 specification [Patent Document 2] JP 2013-69535 A [Patent Document 3] JP 2009-140652 A Summary of the Invention [Problem to be solved by the invention]

[0008] According to the method described in Patent Document 1, by leaving a solvent component in the catalyst layer to the extent that only the bonding surface of the electrolyte membrane with the catalyst layer can be softened, wrinkles are not generated in the electrolyte membrane, and the adhesion between the electrolyte membrane and the catalyst layer can be improved under relaxed thermocompression conditions. However, it is difficult to control the drying so that the amount of remaining solvent is uniform over the entire surface of the catalyst layer while partially removing the solvent in the catalyst solution by heating, and there is a problem that the quality is unstable because there are mixtures of catalyst layers with high interfacial resistance between the electrolyte membrane and the catalyst layer, wrinkles due to deformation of the electrolyte membrane, and cracks on the catalyst layer surface due to differences in the drying state within the catalyst layer. In addition, there is a problem that the margin for the amount of remaining solvent is narrow, which leads to increased costs due to reduced productivity. Furthermore, there is a restriction on the solvent composition of the catalyst solution, so it is difficult to flexibly respond to changes in the type of catalyst layer.

[0009] According to the method described in Patent Document 2, a solution of a binder resin having proton conductivity is applied to the joining surface of the catalyst layer with the electrolyte membrane, and the catalyst layer is joined before the solution dries completely, so that the solution acts as an adhesive, and the adhesion between the electrolyte membrane and the catalyst layer can be improved even at low temperature and low pressure. However, the use of a solution of a binder resin having proton conductivity to join the electrolyte membrane and the catalyst layer leads to an increase in manufacturing costs. Furthermore, there are problems in that the binder resin is the same component as the electrolyte membrane, and the thickness of the electrolyte membrane increases substantially, resulting in an increase in electrical resistance, and that the organic solvent in the solution remains at the interface between the electrolyte membrane and the catalyst layer, which may cause a decrease in power generation performance.

[0010] According to the method described in Patent Document 3, the bonding process involves pressing the bonded bodies including the electrolyte membrane and the bonded bodies including the catalyst layer while immersed in a liquid, and the electrolyte in the electrolyte membrane and the catalyst layer absorbs the liquid sufficiently, and is pressed in a softened state, penetrating into the unevenness of the bonding surfaces of the bonding counterparts, the catalyst layer and the gas diffusion layer, to obtain strong bonding, and the bonding between the layers constituting the membrane-electrode bond can be improved without increasing the temperature or pressure during pressing. However, since the entire members other than the interface involved in the bonding are immersed in the liquid, it is difficult to suppress swelling of the electrolyte membrane and maintain its shape. Furthermore, since the deformation behavior of each member due to drying after bonding is different, it is difficult to obtain a uniform and flat bonded body, and there is also a problem that it is difficult to improve productivity by continuous processing using a roll-shaped long member.

[0011] An object of the present invention is to provide a method for producing a member in which a polymer electrolyte membrane and a gas diffusion layer with a catalyst layer are joined together (hereinafter referred to as a "membrane-electrode assembly"), which can achieve both relaxation of thermocompression bonding conditions (pressing pressure, pressing temperature, pressing time) and improvement of adhesion between the gas diffusion layer with a catalyst layer and the electrolyte membrane with high productivity. [Means for solving the problem]

[0012] In order to solve the above problems, the method for producing a membrane-electrode assembly of the present invention has the following features: The method for producing a membrane-electrode assembly in which a gas diffusion layer with a catalyst layer is bonded to an electrolyte membrane includes a liquid application step of applying a liquid only to the surface of the catalyst layer before bonding in an atmospheric environment, and a thermocompression bonding step of bonding the electrolyte membrane and the gas diffusion layer with the catalyst layer to which the liquid has been applied by thermocompression bonding.

[0013] The apparatus for producing a membrane-electrode assembly of the present invention has the following configuration: The apparatus for manufacturing a membrane-electrode assembly is formed by bonding a gas diffusion layer with a catalyst layer to an electrolyte membrane, and includes a liquid applying means for applying a liquid to the surface of the catalyst layer before bonding, and a thermocompression bonding means for bonding the gas diffusion layer with the catalyst layer to which the liquid has been applied and the electrolyte membrane by thermocompression bonding.

[0014] In the method for producing a membrane-electrode assembly of the present invention, the liquid applied in the liquid application step is preferably a liquid containing water.

[0015] In the method for producing a membrane-electrode assembly of the present invention, the water content in the water-containing liquid is preferably 90% by mass or more and 100% by mass or less.

[0016] In the method for producing a membrane-electrode assembly of the present invention, the liquid applied in the liquid application step is preferably pure water.

[0017] In the method for producing a membrane-electrode assembly of the present invention, the liquid is preferably applied in the form of droplets to the surface of the catalyst layer of the catalyst-layer-attached gas diffusion layer in the liquid application step.

[0018] In the method for producing a membrane-electrode assembly of the present invention, it is preferable that in the liquid applying step, the liquid is applied by spraying.

[0019] In the method for producing a membrane-electrode assembly of the present invention, in the liquid application step, the amount of the liquid in the thermocompression bonding step is 2 It is preferable that the volume is 0.1 μL or more and 5 μL or less per unit area.

[0020] In the method for producing a membrane-electrode assembly of the present invention, a hydrocarbon-based electrolyte membrane is preferably used as the electrolyte membrane.

[0021] The method for producing a membrane-electrode assembly of the present invention preferably includes bonding a catalyst layer-equipped gas diffusion layer to the surface of the electrolyte membrane by any of the methods described above.

[0022] The method for producing a membrane-electrode assembly of the present invention preferably comprises the steps of applying a catalyst solution to one surface of an electrolyte membrane and drying the solution to form a first catalyst layer, and bonding a catalyst-layer-coated gas diffusion layer to the other surface of the electrolyte membrane by any of the methods described above to form a second catalyst layer.

[0023] It is preferable that the method for producing a membrane-electrode assembly of the present invention further comprises a step of covering the first catalyst layer with a cover film, and that the step of forming the second catalyst layer is carried out in a state in which the first catalyst layer is covered with the cover film.

[0024] The method for producing a membrane-electrode assembly of the present invention preferably comprises the steps of applying a catalyst solution to one surface of an electrolyte membrane to form a first catalyst layer, covering the first catalyst layer with a gas diffusion layer before the first catalyst layer is dried, drying the catalyst layer through the gas diffusion layer, and bonding a catalyst layer-coated gas diffusion layer to the other surface of the electrolyte membrane by any one of the methods described above to form a second catalyst layer.

[0025] In the apparatus for producing a membrane-electrode assembly of the present invention, the liquid applying means is preferably a means for applying the liquid in the form of droplets to the surface of the catalyst layer.

[0026] In the apparatus for producing a membrane-electrode assembly of the present invention, the liquid applying means is preferably a spray. Effect of the Invention

[0027] According to the present invention, it is possible to manufacture a membrane-electrode assembly while simultaneously achieving relaxation of thermocompression bonding conditions (pressing pressure, pressing temperature, pressing time) and improvement of adhesion between a catalyst layer-attached gas diffusion layer and an electrolyte membrane with high productivity. [Brief description of the drawings]

[0028] [Figure 1] 1 is a side view showing a schematic configuration of a first embodiment of a membrane-electrode assembly manufacturing apparatus of the present invention. [Diagram 2] FIG. 4 is a side view showing a schematic configuration for forming a first catalyst layer in a second embodiment of a membrane-electrode assembly manufacturing apparatus of the present invention. [Diagram 3] FIG. 4 is a side view showing a schematic configuration for forming a second catalyst layer in a second embodiment of a membrane-electrode assembly manufacturing apparatus of the present invention. [Figure 4] FIG. 11 is a side view showing a schematic configuration for forming a first catalyst layer in a third embodiment of a membrane-electrode assembly manufacturing apparatus of the present invention. [Diagram 5] FIG. 11 is a side view showing a schematic configuration for forming a second catalyst layer in a third embodiment of a membrane-electrode assembly manufacturing apparatus of the present invention. [Figure 6] 1 is a side view showing a schematic configuration for explaining a heat shield in a first embodiment of a membrane-electrode assembly manufacturing apparatus of the present invention.

[0023] FIG. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0029] Although the present invention is not limited thereto, the following is considered as the function of the present invention. In the thermocompression bonding process, the electrolyte membrane and the catalyst-layered gas diffusion layer are pressed together in a state where a liquid is applied to the bonding surface of the catalyst-layered gas diffusion layer with the electrolyte membrane, so that the air present at the interface is expelled and only liquid exists between the electrolyte membrane and the catalyst-layered gas diffusion layer. In this state, the liquid is evaporated and the interface is evacuated, improving the adhesion between the catalyst-layered gas diffusion layer and the electrolyte membrane. Furthermore, the electrolyte membrane is softened by contact with the liquid, so that the adhesion between the two is further improved. Note that while the electrolyte membrane is in contact with the liquid, it is held by the pressure during thermocompression bonding, so that swelling can be prevented. The liquid evaporated at the interface is discharged to the outside of the membrane-electrode assembly by passing through the pores of the catalyst-layered gas diffusion layer having a porous structure.

[0030] In this specification, the term "membrane-electrode assembly" refers to a member in which an electrolyte membrane is joined to a gas diffusion layer, for example, a gas diffusion layer with a catalyst layer formed on one side of a substrate (gas diffusion layer) made of gas-permeable carbon paper or the like, that is, a gas diffusion electrode, and in addition, since attention is focused on the joining surface between the electrolyte membrane and the catalyst layer, this is included in the technical field of "membrane-catalyst assembly."

[0031] In addition, the "manufacturing of a membrane-electrode assembly" also includes an operation of bonding a gas diffusion layer with a catalyst layer to one side of an electrolyte membrane on which a catalyst layer has already been formed, and an operation of bonding a gas diffusion layer with a catalyst layer to one side of an electrolyte membrane and then forming a catalyst layer on the other side. Methods for forming a catalyst layer on one or the other side of the above-mentioned electrolyte membrane include, for example, a method of directly applying a catalyst layer or a method of transferring a catalyst layer using a catalyst layer transfer sheet.

[0032] [Electrolyte membrane] The electrolyte membrane to be used in the manufacturing method and manufacturing apparatus for the membrane-electrode assembly of the present invention is not particularly limited as long as it has proton conductivity and operates as an electrolyte membrane for use in a solid polymer electrolyte fuel cell, a solid polymer electrolyte membrane water electrolysis device, an electrochemical hydrogen pump, etc., and known or commercially available electrolyte membranes can be used. As such an electrolyte membrane, a polymer electrolyte membrane is preferable, and for example, a fluorine-based electrolyte membrane made of perfluorosulfonic acid or a hydrocarbon-based electrolyte membrane made of a hydrocarbon polymer having proton conductivity imparted to a hydrocarbon skeleton can also be used.

[0033] In particular, since hydrocarbon-based electrolyte membranes have a higher glass transition temperature and are subject to greater shrinkage and deformation when heated than fluorine-based electrolyte membranes, it is often difficult to find transfer conditions that provide excellent productivity using conventional thermocompression bonding methods, and the manufacturing method and manufacturing apparatus of the present invention can be suitably applied to these membranes.

[0034] Furthermore, as the electrolyte membrane, a composite electrolyte membrane in which a polymer electrolyte and a porous substrate are composited can be used.

[0035] [Composite electrolyte membrane] The composite electrolyte membrane is a composite of a polymer electrolyte and a porous substrate, and can be obtained, for example, by filling (impregnating) a porous substrate with a polymer electrolyte. Examples of the porous substrate include a hydrocarbon-based porous substrate mainly composed of a hydrocarbon-based polymer compound, and a fluorine-based porous substrate mainly composed of a fluorine-based polymer compound.

[0036] Examples of the hydrocarbon polymer compound include polyethylene (PE), polypropylene (PP), polystyrene (PS), polyacrylate, polymethacrylate, polyvinyl chloride (PVC), polyvinylidene chloride (PVdC), polyester, polycarbonate (PC), polysulfone (PSU), polyethersulfone (PES), polyphenylene oxide (PPO), polyarylene ether polymer, polyphenylene sulfide (PPS), polyphenylene sulfide sulfone, polyparaphenylene (PPP), polyarylene polymer, polyarylene ketone, polyether ketone (PEK), polyarylene phosphine oxide, polyether phosphine oxide, polybenzoxazole (PBO), polybenzothiazole (PBT), polybenzimidazole (PBI), polyamide (PA), polyimide (PI), polyetherimide (PEI), and polyimide sulfone (PIS).

[0037] Examples of fluorine-based polymer compounds include polytetrafluoroethylene (PTFE), polyhexafluoropropylene, tetrafluoroethylene-hexafluoropropylene copolymer (FEP), ethylene-tetrafluoroethylene copolymer (ETFE), polyvinylidene fluoride (PVdF), polychlorotrifluoroethylene (PCTFE), perfluoroalkoxy fluorine resin (PFA), and ethylene-chlorotrifluoroethylene copolymer (ECTFE).

[0038] From the viewpoints of water resistance, chemical resistance, and mechanical properties, PE, PP, PPS, PEK, PBI, PTFE, polyhexafluoropropylene, FEP, and PFA are preferred, and further from the viewpoint of chemical resistance and chemical durability, PTFE, polyhexafluoropropylene, FEP, and PFA are more preferred, with PTFE being particularly preferred since it has high mechanical strength due to molecular orientation.

[0039] The composite electrolyte membrane is particularly preferably a composite of a hydrocarbon electrolyte and a fluorine-based porous substrate. In this case, by adding a nonionic fluorine-based surfactant to the hydrocarbon electrolyte solution during the composite formation, the fluorine-based porous substrate can be easily filled (impregnated) with the hydrocarbon electrolyte with high efficiency without gaps.

[0040] The composite electrolyte membrane can be produced, for example, by impregnating a porous substrate with a polymer electrolyte solution, and then drying the substrate to remove the solvent contained in the polymer electrolyte solution. Examples of the impregnation method include the following methods.

[0041] (1) A method of controlling the membrane thickness by removing excess solution while pulling up a porous substrate immersed in a polymer electrolyte solution; (2) A method of casting a polymer electrolyte solution onto a porous substrate, (3) A method in which a porous substrate is attached onto a polymer electrolyte solution cast onto a supporting substrate, and the substrate is impregnated with the polymer electrolyte solution.

[0042] [Catalyst layer] The catalyst layer to be used in the production method and production apparatus for the membrane-electrode assembly of the present invention is not particularly limited as long as it operates as a catalyst layer for use in a solid polymer fuel cell, a solid polymer electrolyte membrane water electrolysis device, an electrochemical hydrogen pump, etc. In general, a catalyst layer having a porous structure composed of conductive particles such as carbon particles, catalyst particles such as platinum particles or platinum alloy particles supported on the conductive particles, and an electrolyte component such as an ionomer having proton conductivity can be used.

[0043] As an example, suitable conductive particles include oil furnace black, gas furnace black, acetylene black, thermal black, graphite, carbon nanotubes, graphene, and other carbons, metal oxides such as tin oxide and titanium oxide, etc. Suitable catalyst particles include platinum, iridium, ruthenium, rhodium, palladium, and other noble metals, alloys of platinum with manganese, iron, cobalt, nickel, copper, zinc, and other metals, ternary alloys of platinum and ruthenium, iridium oxide, and the like. Suitable electrolyte components include perfluorocarbon sulfonic acid polymers such as "Nafion" (registered trademark, manufactured by Chemours), "Aquivion" (registered trademark, manufactured by Solvay), "Flemion" (registered trademark, manufactured by Asahi Glass Co., Ltd.), "Aciplex" (registered trademark, manufactured by Asahi Kasei Corporation), and "Fumion" F (registered trademark, manufactured by FuMA-Tech), as well as hydrocarbon polymers such as polysulfone sulfonic acid, polyaryl ether ketone sulfonic acid, polybenzimidazole alkyl sulfonic acid, polybenzimidazole alkyl phosphonic acid, polystyrene sulfonic acid, polyether ether ketone sulfonic acid, and polyphenyl sulfonic acid.

[0044] The catalyst solution is a dispersion of the catalyst layer material in a solvent that evaporates by drying, and is not particularly limited as long as it is sufficient to form a catalyst layer on the electrolyte membrane. In general, the solvent is preferably water, alcohol such as methanol, ethanol, 1-propanol, 2-propanol, tert-butanol, ethylene glycol, N,N-dimethylformamide, N-methyl-2-pyrrolidone, or the like.

[0045] [Gas diffusion layer] The gas diffusion layer used in the method and apparatus for producing the membrane-electrode assembly of the present invention is not particularly limited as long as it operates as a gas diffusion layer for use in a solid polymer fuel cell, a solid polymer electrolyte membrane water electrolysis device, an electrochemical hydrogen pump, etc. In general, a material having low electrical resistance, capable of collecting or supplying electricity, and capable of forming a catalyst layer can be used. Examples of the material constituting the gas diffusion layer include carbonaceous materials and conductive inorganic materials, such as a sintered material from polyacrylonitrile, a sintered material from pitch, carbon materials such as graphite and expanded graphite, stainless steel, molybdenum, and titanium. The form of these materials is not particularly limited, and they are used in, for example, a fibrous or particulate form, but fibrous conductive materials (conductive fibers) such as carbon fibers are preferred from the viewpoint of fuel permeability. As the gas diffusion layer using conductive fibers, either a woven fabric or a nonwoven fabric structure can be used. As such woven fabric, a plain weave, a twill weave, a satin weave, a patterned weave, a tapestry weave, etc. can be used without any particular limitation. The nonwoven fabric may be made by any method, including papermaking, needle punching, spunbonding, water jet punching, and melt blowing, without any particular limitation. Knitted fabrics may also be used. In particular, when carbon fibers are used in these fabrics, preferred are woven fabrics made by carbonizing or graphitizing plain weave fabrics made of flame-resistant spun yarns, nonwoven fabrics made by carbonizing or graphitizing flame-resistant yarns after processing them into nonwoven fabrics by needle punching or water jet punching, and matte nonwoven fabrics made by papermaking using flame-resistant yarns, carbonized yarns, or graphitized yarns. In particular, it is preferred to use nonwoven fabrics or cloths, since they are thin and strong. Examples of carbon fibers used in such gas diffusion layers include polyacrylonitrile (PAN)-based carbon fibers, phenol-based carbon fibers, pitch-based carbon fibers, and rayon-based carbon fibers. Examples of such carbon fibers include, for example, Toray Industries, Inc.'s carbon paper TGP series and SO series, and E-TEK's carbon cloth.

[0046] In addition, such gas diffusion layer may be subjected to water repellent treatment to prevent deterioration of gas diffusion and permeability due to water retention, partial water repellent treatment to form a water drainage path, hydrophilic treatment, addition of carbon powder to reduce resistance, platinum plating to impart potential corrosion resistance, etc. In addition, a conductive intermediate layer containing at least an inorganic conductive material and a hydrophobic polymer may be provided between the electrode substrate and the catalyst layer. In particular, when the electrode substrate is a carbon fiber woven fabric or nonwoven fabric with a large porosity, the provision of a conductive intermediate layer can suppress performance degradation caused by the catalyst solution permeating into the gas diffusion layer.

[0047] [Gas diffusion layer with catalyst layer] The gas diffusion layer with a catalyst layer to be used in the manufacturing method and manufacturing apparatus for the membrane-electrode assembly of the present invention is not limited as long as the catalyst layer is formed on the gas diffusion layer. In general, the catalyst solution may be directly applied to the gas diffusion layer and dried. Alternatively, the catalyst solution may be applied once to a temporary substrate separate from the gas diffusion layer, dried and formed into a sheet, which is then thermocompressed to the gas diffusion layer, and the temporary substrate is removed.

[0048] [Liquid application step] The liquid application step is a step of applying a liquid to the catalyst layer surface of the catalyst layer-attached gas diffusion layer before bonding, i.e., the bonding surface with the electrolyte membrane. Applying a liquid means forming a state in which the liquid is exposed and attached to the catalyst layer surface of the catalyst layer-attached gas diffusion layer. It is preferable that the liquid is not substantially allowed to penetrate into the catalyst layer. If the liquid is not allowed to penetrate into the catalyst layer, there is no risk of the electrolyte component in the catalyst layer being dissolved, the strength of the catalyst layer is not reduced, and the occurrence of cracks in the thermocompression bonding step can be effectively prevented.

[0049] In the liquid application process, the liquid is applied only to the surface of the catalyst layer in an atmospheric environment. By applying the liquid only to the surface of the catalyst layer, the number of process control parameters is reduced compared to applying the liquid to both the catalyst layer and the electrolyte membrane, which has the advantages of stabilizing the manufacturing conditions and making it easier to control and manage the amount of liquid applied to the bonding surface, as well as suppressing variations in the amount of liquid on the bonding surface caused by droplets coming into contact with each other before the thermocompression bonding process.

[0050] Furthermore, by applying the liquid under an atmospheric environment, it is possible to apply the liquid only to the surface of the catalyst layer, and it is possible to suppress the penetration of the liquid into the inside of the catalyst layer. By suppressing the penetration of the liquid into the inside of the catalyst layer, it is possible to effectively suppress the decrease in strength of the catalyst layer and the occurrence of cracks. Since the liquid that has penetrated into the inside of the catalyst layer does not contribute to improving the adhesion at the interface, and rather increases the energy consumption for evaporating it, suppressing the penetration of the liquid into the inside of the catalyst layer is also effective in terms of production costs.

[0051] In the liquid application step, the liquid is not particularly limited as long as it is a material that evaporates by heating in the subsequent thermocompression bonding step and is not toxic to the electrolyte membrane and the gas diffusion layer with catalyst layer. For example, water, alcohols such as methanol, ethanol, 1-propanol, 2-propanol, tert-butanol, and mixtures thereof can be used, but it is preferable to use a liquid containing at least water. If the liquid undergoes a sudden temperature change during thermocompression bonding, wrinkles may occur in the electrolyte membrane, but since water has a higher boiling point and specific heat than the above alcohols and the temperature rise during thermocompression bonding is gradual, such damage can be suppressed if the liquid contains water. In addition, since water has a lower permeability into the catalyst layer than alcohol, it is possible to prevent the occurrence of cracks due to the liquid permeating into the catalyst layer. Furthermore, by using a liquid containing water, the present invention can be implemented at low cost, and the environmental burden during production can be reduced. Note that even if liquid remains in the membrane-electrode assembly bonded by the manufacturing method and manufacturing apparatus of the present invention, if it is water, it will not affect the performance of the device using it. The water content of the water-containing liquid is more preferably 50% by mass to 100% by mass, even more preferably 90% by mass to 100% by mass, and even more preferably 100% by mass. In other words, it is most preferable to use pure water as the liquid. Here, pure water refers to high-purity water that does not contain impurities, and refers to water of JIS K 0557 (1998) A4 level obtained by a commercially available pure water production device in which water is collected through a reverse osmosis membrane and an ion exchange resin, or water of equivalent quality.

[0052] The liquid may contain solid materials in a dissolved or dispersed state, so long as the liquid as a whole has fluidity and the effects of the present invention can be obtained.

[0053] In the liquid application step, the method of applying the liquid is not particularly limited, and examples of the method include a method of forming a uniform coating film on the surface of the catalyst layer using a gravure coater, die coater, comma coater, etc., and a method of applying the liquid to the surface of the catalyst layer in the form of droplets. The method of applying the liquid to the surface of the catalyst layer in the form of droplets is particularly preferred. Here, the droplet form refers to a state in which countless droplets are attached to the surface of the catalyst layer. Note that a droplet is a mass of liquid that is held together by surface tension and has a size of 1 cm on the catalyst layer. 2 If the liquid is applied in droplets, it is possible to apply a small amount of liquid, the minimum amount necessary to soften the electrolyte membrane during bonding, uniformly to the bonding surface. 2 This means that the total amount of liquid applied around the catalyst layer is the same at each position. Even liquids such as water, which are easily repelled by the catalyst layer and difficult to form a uniform coating film, can be applied easily if they are in droplet form. Furthermore, since the contact area with the catalyst layer is small if the liquid is in droplet form, it is possible to minimize the penetration of the liquid into the catalyst layer until it is thermocompressed. Note that the pressure applied during the thermocompression process causes the droplets to spread out at the interface and bond with the surrounding droplets, making it possible to soften the electrolyte membrane on all sides of the interface.

[0054] In the liquid application process, the amount of liquid at the start of the thermal compression process is set to 1 cm 2 It is preferable to apply liquid in an amount of 0.1 μL to 5 μL per cm2 of the catalyst layer. When the amount of liquid in the thermocompression bonding step is within the above-mentioned preferred range, the electrolyte membrane can be sufficiently softened, adhesion is sufficient, and there is no risk of the electrolyte membrane being left unsoftened in parts due to partial liquid droplets not bonding when pressed in the thermocompression bonding step, while no liquid drips during transportation, and since almost all of the liquid evaporates due to heating during thermocompression bonding, there is no risk of the electrolyte membrane swelling due to the liquid remaining at the interface the moment the pressure is removed. It is more preferable that the amount of liquid is within the above-mentioned preferred range. 2The amount of liquid is 0.1 μL to 0.8 μL per cm. The amount of liquid is determined by attaching a sample piece of a PET film or the like whose weight has been measured to the surface of the catalyst layer of the gas diffusion layer with a catalyst layer so as to be laminated with the catalyst layer, applying liquid in the liquid application step, and then removing the sample piece with the liquid just before the sample piece and the electrolyte membrane come into contact in the thermocompression bonding step, and measuring its weight. 2 The size of the sample can be measured by calculating the volume of liquid around the sample. The size of the sample can be a square with sides of 1 to 10 cm.

[0055] In addition, the smaller the average diameter of the applied droplets, the more preferable, specifically, the smaller the diameter of the droplets when attached to the catalyst layer surface is, since the distance between the droplets can be shortened as the average diameter is smaller, the droplets can be bonded with a smaller amount of liquid when pressed in the thermocompression bonding process.

[0056] In the liquid application step, the means for applying the liquid in the form of droplets is not particularly limited, and may include a method of spraying droplets by a spray or inkjet, a method of condensing droplets on the joining surface in a humid atmosphere, a method of spraying a mist of liquid by an ultrasonic vibrator, etc., but a method of spraying droplets by a spray is preferred in that the liquid can be applied efficiently while controlling the amount of liquid. In addition, the spray for spraying droplets is not particularly limited, and may include a two-fluid spray nozzle that atomizes and sprays the liquid by compressed air.

[0057] When using a means for applying the liquid in the form of droplets as described above, it is preferable to surround the liquid application means such as a spray nozzle with a chamber in order to prevent the droplets from scattering around. Although it is not necessary to reduce the pressure inside the chamber, it is preferable to reduce the pressure slightly to a negative pressure relative to atmospheric pressure, since this prevents the droplets from scattering around from the gap between the chamber and the catalyst layer.

[0058] [Thermocompression bonding process] The catalyst layer-attached gas diffusion layer that has been subjected to the liquid application step is then subjected to a thermocompression bonding step in which the catalyst layer-attached gas diffusion layer and the electrolyte membrane are bonded to each other by heating and clamping the catalyst layer-attached gas diffusion layer and the electrolyte membrane in a laminated state in which the liquid-applied surface of the catalyst layer-attached gas diffusion layer and the electrolyte membrane are in contact with each other.

[0059] In the thermocompression bonding step, the time from when the catalyst layer-attached gas diffusion layer and the electrolyte membrane come into contact with each other until a clamping pressure is applied thereto is preferably 0.1 seconds or less. If this time is within the above-mentioned preferred range, the electrolyte membrane is unlikely to swell due to the adhesion of liquid, and the adhesion of liquid and the fixation of the electrolyte membrane by thermocompression are performed almost simultaneously, so that swelling can be suppressed.

[0060] The heating temperature in the thermocompression bonding process is not particularly limited, but is preferably from the boiling point of the liquid applied to the catalyst layer-attached gas diffusion layer (hereinafter referred to as the "liquid boiling point") to 220°C. The heating temperature is the maximum temperature reached at the bonding surface between the electrolyte membrane and the catalyst layer during the thermocompression bonding process, and a thermocouple can be used for measurement. When the heating temperature is in the above-mentioned preferred range, it does not take much time for the liquid to evaporate, resulting in excellent productivity, while there is no risk of the electrolyte membrane being damaged by heat. The heating temperature in the thermocompression bonding process is more preferably from the liquid boiling point to 160°C. The liquid boiling point is the boiling point when the external pressure is 1 atmosphere, and when the evaporated liquid is a single composition, it means the boiling point of that liquid, and when it is a mixture, it means the value of the component of the mixture with the highest boiling point as a single unit.

[0061] The pressure applied to the electrolyte membrane and catalyst layer in the thermocompression bonding process can be set as appropriate, but is preferably 1 MPa or more and 20 MPa or less. In the above preferred range, the electrolyte membrane and the catalyst layer-attached gas diffusion layer can be sufficiently adhered to each other, while excessive pressure is not applied to the catalyst layer-attached gas diffusion layer or the electrolyte membrane, so that the structure of the catalyst layer-attached gas diffusion layer is not destroyed, mechanical damage to the electrolyte membrane is not large, and there is no risk of deterioration in durability or power generation performance. The pressure in the thermocompression bonding process is more preferably 1 MPa to 10 MPa.

[0062] The pressing form in the thermocompression step is not particularly limited, and may be a line contact form in which the electrolyte membrane and the gas diffusion layer with the catalyst layer are in contact in a single line, as in the case of a hot press roll, or a surface contact form in which the electrolyte membrane and the gas diffusion layer with the catalyst layer are in contact in a planar manner with a width in the transport direction, as in the case of a double belt press mechanism.

[0063] [Roll-to-roll manufacturing method] The method for producing a membrane-electrode assembly of the present invention is preferably carried out by a roll-to-roll system, that is, a system in which the liquid application step and the thermocompression bonding step are carried out continuously by the roll-to-roll system.

[0064] The roll-to-roll manufacturing method is a manufacturing method in which, for example, a long roll of an electrolyte membrane and a long roll of a gas diffusion layer with a catalyst layer are continuously unwound and transported, and the membrane-electrode assembly obtained by carrying out a liquid application step and a heat-pressure bonding step is wound into a roll.

[0065] The manufacturing apparatus for a membrane-electrode assembly, which will be described later, is an example of a manufacturing apparatus capable of implementing a roll-to-roll type manufacturing method.

[0066] The above is an explanation of the manufacturing method of the present invention, but as will be easily understood from the above explanation and the description of the embodiments below, this specification also discloses a manufacturing apparatus as described below for carrying out the manufacturing method. (1) A manufacturing apparatus for a membrane-electrode assembly in which a gas diffusion layer with a catalyst layer is bonded to an electrolyte membrane, the manufacturing apparatus for a membrane-electrode assembly having a liquid applying means for applying a liquid to a surface of the catalyst layer before bonding, and a thermocompression bonding means for bonding the gas diffusion layer with the catalyst layer to which the liquid has been applied and the electrolyte membrane by thermocompression bonding; (2) The apparatus for producing a membrane-electrode assembly according to (1), wherein the liquid supplying means is a means for supplying the liquid in the form of droplets onto a surface of a catalyst layer. (3) The apparatus for producing a membrane-electrode assembly according to (2), wherein the liquid applying means is a spray.

[0067] Hereinafter, specific embodiments of the present invention will be described with reference to schematic diagrams of a manufacturing apparatus for implementing the manufacturing method of the present invention. Note that the following description is provided to facilitate understanding of the present invention and does not limit the present invention in any way, but as will be easily understood by those skilled in the art, references to preferred aspects and modifications of aspects in each embodiment can be interpreted as descriptions of the manufacturing method or manufacturing apparatus of the present invention as a higher-level concept. Note that in this specification, for convenience, the top of each drawing is described as "upper" and the bottom as "lower," but the up-down direction of each drawing is not necessarily limited to the vertical direction relative to the ground.

[0068] [First embodiment: Production of membrane-electrode assembly 1] FIG. 1 is a side view showing a schematic configuration of a membrane-electrode assembly manufacturing apparatus of the present invention.

[0069] In the membrane-electrode assembly manufacturing apparatus 100 according to this embodiment, the membrane-electrode assembly is manufactured as follows.

[0070] The electrolyte membrane 10 is unwound from an electrolyte membrane supply roll 11 and supplied to a thermocompression bonding section P through a guide roll 12. Above and below the unwound electrolyte membrane 10, catalyst layer-attached gas diffusion layer supply rolls 21A and 21B are provided, respectively. The catalyst layer-attached gas diffusion layer bonded to the upper surface of the electrolyte membrane 10 is formed using a catalyst layer-attached gas diffusion layer 20A. The catalyst layer-attached gas diffusion layer 20A is prepared in advance by, for example, applying a catalyst solution to the gas diffusion layer, and is unwound from a catalyst layer-attached gas diffusion layer supply roll 21A and transported by a backup roll 31A and a guide roll 22A in this order, while the gas diffusion layer side opposite to the catalyst layer-forming surface is supported by each of them. The catalyst layer-attached gas diffusion layer 20B for forming the catalyst layer-attached gas diffusion layer formed on the lower surface of the electrolyte membrane 10 is unwound from a catalyst layer-attached gas diffusion layer supply roll 21B and transported by a backup roll 31B and a guide roll 22B in this order, while the gas diffusion layer side is supported by each of them. In this manner, the catalyst-layer-attached gas diffusion layers 20A and 20B are supplied to the thermocompression bonding section P so that the surfaces on which the catalyst layers are formed face the electrolyte membrane 10.

[0071] The gas diffusion layer has air permeability. Air permeability means that the layer has a property of being able to transmit gas, for example, pores that are connected in the thickness direction. By having air permeability, the vapor of the liquid generated during thermocompression bonding can be effectively discharged.

[0072] For the guide rolls 12, 22A, 22B, in order to remove wrinkles and slack in the electrolyte membrane 10 and catalyst layer-attached gas diffusion layers 20A, 21B supplied to the thermocompression bonding section P, it is preferable to use expander rolls.

[0073] The manufacturing apparatus 100 for the membrane-electrode assembly according to this embodiment is configured to bond the catalyst layer-equipped gas diffusion layers to both sides of the electrolyte membrane 10, but may be configured to bond the catalyst layer-equipped gas diffusion layer to only one side of the electrolyte membrane 10.

[0074] By bonding a catalyst layer-equipped gas diffusion layer to only one side of the electrolyte membrane, it is possible to impart functionality by sandwiching a frame-shaped cutout film before bonding a catalyst layer-equipped gas diffusion layer to the other side of the electrolyte membrane. Alternatively, it is possible to cut the electrolyte membrane to the desired dimensions with a catalyst layer-equipped gas diffusion layer bonded to only one side of the electrolyte membrane, and then bond it to a frame-shaped film material or a catalyst layer-equipped gas diffusion layer to create a single MEA.

[0075] In this embodiment, a spray nozzle 30A is provided facing the catalyst layer-equipped gas diffusion layer 20A supported on a backup roll 31A. The spray nozzle 30A has an outlet directed toward the central axis of the backup roll 31A and is provided at a predetermined distance from the backup roll 31A. One or more spray nozzles 30A are provided in the width direction of the catalyst layer-equipped gas diffusion layer 20A according to the substrate width of the catalyst layer-equipped gas diffusion layer 20A.

[0076] The spray nozzle 30A is supplied with water from a water supply tank (not shown), and discharges the supplied water from a discharge port to apply droplets to the bonding surface of the catalyst layer-attached gas diffusion layer with the electrolyte membrane.

[0077] Furthermore, the spray nozzle 30A and the space S in which the droplets fly from the discharge port of the spray nozzle 30A to the catalyst layer-attached gas diffusion layer are surrounded by a nozzle chamber 32A, and a pressure reduction tank 34A that reduces the pressure in the space S is connected to the nozzle chamber 32A by piping via a valve 33A that switches between pressure reduction. The pressure reduction tank 34A makes the space S negative relative to the environmental pressure of the manufacturing apparatus, so that a small amount of outside air is sucked in through a gap between the nozzle chamber 32A and the catalyst layer-attached gas diffusion layer 20A, preventing excess droplets from the spray nozzle 30A from scattering around. The water that accumulates in the nozzle chamber 32A is discharged from a drain (not shown) provided in the nozzle chamber 32A and returned to a water supply tank for reuse.

[0078] The above is an explanation of the liquid application means for the catalyst layer-coated gas diffusion layer 20A. However, the liquid application means (spray nozzle 30B, nozzle chamber 32B, valve 33B, and reduced pressure tank 34B) provided for the catalyst layer-coated gas diffusion layer 20B have the same configuration, so their explanations are omitted.

[0079] The nozzle chambers 32A and 32B do not need to be depressurized, but a small reduction in pressure is preferable because it can prevent droplets from scattering to the surroundings. In this case, if the degree of reduction in pressure is too large, the amount of outside air sucked into the nozzle chambers 32A and 32B increases, which may disturb the air flow in the nozzle chambers 32A and 32B and reduce the accuracy of applying droplets. Therefore, the degree of reduction in pressure in the nozzle chambers 32A and 32B is, for example, appropriate in the range of up to -50.0 kPa with respect to the environmental pressure (atmospheric pressure) of the manufacturing apparatus, preferably up to -10.0 kPa, and more preferably up to -5.0 kPa.

[0080] In this way, the electrolyte membrane 10 and the catalyst layer-attached gas diffusion layers 20A, 20B with the liquid applied to the bonding surface with the electrolyte membrane 10 are supplied to the thermocompression bonding section P and pass between the heat press rolls 40A, 40B. As shown in Fig. 6, it is preferable to provide heat shields 41A, 41B between the catalyst layer-attached gas diffusion layer 20A and the heat press roll 40A, and between the catalyst layer-attached gas diffusion layer 20B and the heat press roll 40B, respectively. By providing the heat shields 41A, 41B, it is possible to prevent the liquid applied to the catalyst layer-attached gas diffusion layers 20A, 20B from evaporating before heat pressing due to the radiant heat radiated from the heat press rolls 40A, 40B.

[0081] The hot press rolls 40A and 40B are connected to a driving means (not shown) and can be rotated while controlling the speed. The hot press rolls 40A and 40B rotate at a constant speed while applying heat and pressure to the electrolyte membrane 10 and the catalyst layer-attached gas diffusion layers 20A and 20B, and thus the electrolyte membrane 10 and the catalyst layer-attached gas diffusion layers 20A and 20B are transported at synchronized transport speeds, and the catalyst layer-attached gas diffusion layers are thermocompression-bonded to both sides of the electrolyte membrane 10 to form the membrane-electrode assembly 13a. Note that illustrations of heating devices, pressure devices, etc. for the hot roll presses 40A and 40B are omitted.

[0082] The material of the heat press rolls 40A and 40B is not particularly limited, but it is preferable that one roll is made of a metal such as stainless steel, and the other roll is coated on the surface with an elastic material such as a resin or elastomer material such as rubber. By making one of the heat press rolls 40A and 40B a metal, it is possible to sufficiently heat the electrolyte membrane and the catalyst layer-attached gas diffusion layer, and by making the surface layer of the other press roll an elastic material, the press roll flexibly deforms with respect to the catalyst layer-attached gas diffusion layers 20A and 20B, and good linear contact is maintained, making it possible to uniformize the linear pressure in the substrate width direction.

[0083] As the material of the elastic body, for example, when rubber is used, fluororubber, silicone rubber, EPDM (ethylene propylene diene rubber), neoprene, CSM (chlorosulfonated polyethylene rubber), urethane rubber, NBR (nitrile rubber), ebonite, etc. can be used. In addition, the rubber hardness of the elastic body is preferably in the range of 70 to 97° in Shore A standard. When the rubber hardness of the elastic body is in the above-mentioned preferable range, the deformation amount of the elastic body is appropriate, the clamping contact width with the catalyst layer-attached gas diffusion layers 20A, 20B is not too large, and the pressure required for bonding the electrolyte membrane 10 and the catalyst layer can be secured, while the clamping contact width is not too small, and the clamping time required for bonding can be secured.

[0084] As a heating means for the hot press rolls 40A and 40B, various heaters, steam, oil, and other heat transfer media can be used, but are not particularly limited. The heating temperatures of the upper and lower rolls may be the same or different.

[0085] The method of controlling the clamping pressure of the hot press rolls 40A and 40B is not particularly limited, and the clamping pressure may be controlled using a pressure means such as a hydraulic cylinder, or a constant gap may be provided between the hot press rolls 40A and 40B by position control using a servo motor or the like, and the clamping pressure may be controlled according to the size of the gap.

[0086] In this embodiment, the heat press rolls 40A and 40B, which are a line contact mechanism, are used in the thermocompression bonding section P, but the present invention is not limited to this. A mechanism in which the electrolyte membrane 10 and the catalyst layer-attached gas diffusion layers 20A and 20B are pressed by a plurality of line contacts using a plurality of rolls may be used, or a double belt press mechanism in which pressing is performed by surface contact may be used. When a plurality of sets of rolls are used, the number of rolls is not particularly limited, but 2 to 10 sets are preferable.

[0087] In this manner, the electrolyte membrane 10 passes through the thermocompression bonding section P, and the catalyst layer-equipped gas diffusion layers are bonded to both sides of the electrolyte membrane 10 to form a membrane-electrode assembly 13a.

[0088] The delivery roll 14 can be connected to a driving means not shown, and when the press rolls 40A, 40B are not clamping the electrolyte membrane 10 and the catalyst layer-equipped gas diffusion layers 20A, 20B, the electrolyte membrane 10 can be transported by controlling the speed.

[0089] Also, a heating means (not shown) can be provided for heating the membrane-electrode assembly 13a in which catalyst layers are bonded to both sides of the electrolyte membrane in the thermocompression bonding section P. The heating means can be provided, for example, between the thermocompression bonding section P and the delivery roll 14. As the heating means, hot air or a heating roll can be used. The hot air temperature or the surface temperature of the heating roll is suitably, for example, 120°C to 250°C, and preferably 150°C to 230°C.

[0090] [Second embodiment: Production of membrane-electrode assembly 2] In the second embodiment, first, a first catalyst layer is formed on one side of an electrolyte membrane by a catalyst layer forming apparatus 101 shown in Fig. 2. The first catalyst layer is formed as follows.

[0091] In this embodiment, the electrolyte membrane 10' is supported on a support and supplied to the catalyst layer forming apparatus 101. The material of the support for the electrolyte membrane is not particularly limited, but for example, a PET film can be used.

[0092] The electrolyte membrane 10' with the support is unwound from an electrolyte membrane supply roll 11 and supplied to a catalyst solution coating means 72 through a guide roll 12. The catalyst solution coating means 72 is provided facing the electrolyte membrane 10' supported on a backup roll 73. The catalyst solution coating means 72 receives catalyst solution from a catalyst solution tank 70 using a catalyst solution delivery pump 71, and forms a coating film by coating the supplied catalyst solution on the electrolyte membrane. The method of coating the catalyst solution in the catalyst solution coating means 72 is not particularly limited. Methods such as a gravure coater, a die coater, a comma coater, a roll coater, a spray coater, and a screen printing method can be used.

[0093] In this embodiment, the catalyst layer is formed by applying a catalyst solution to the electrolyte membrane 10', but the catalyst layer may be transferred and formed on the electrolyte membrane 10' using a catalyst layer transfer sheet.

[0094] Next, the coating film of the catalyst solution formed on the electrolyte membrane is dried by drying means 74, and the solvent in the catalyst solution is evaporated to form a dried first catalyst layer. The method of drying the catalyst solution in drying means 74 is not particularly limited. A method of blowing a heat medium such as hot air, a thermal oven method using a heater, or the like can be used.

[0095] The membrane / first catalyst layer assembly 16 in which the first catalyst layer is formed on the electrolyte membrane in this manner is delivered by a delivery roll 14 and taken up in a roll by a take-up roll 17 with the support attached.

[0096] Next, a second catalyst layer is formed on the surface of the electrolyte membrane opposite to the surface on which the first catalyst layer has been formed, by a membrane-electrode assembly manufacturing apparatus 102 according to the embodiment shown in Fig. 3. The second catalyst layer is formed as follows.

[0097] The membrane / first catalyst layer assembly 16 is unwound from the supply roll 18, passes through the guide roll 12, and is further passed through guide rolls 26A and 26B, whereby the support 51 is peeled off from the interface with the electrolyte membrane. The peeled support 51 is taken up by the support take-up roll 50.

[0098] A cover film 61 unwound from a cover film supply roll 60 is laminated onto the first catalyst layer surface of the membrane / first catalyst layer assembly 16 from which the support 51 has been peeled off via guide rolls 27A and 27B, and then the assembly is supplied to a thermocompression bonding section P. Note that the lamination of the cover film 61 may be performed before the support 51 is peeled off.

[0099] The cover film 61 is used to protect the first catalyst layer during the process of forming the second catalyst layer, and the material is not particularly limited as long as the function of the catalyst layer is not impaired by attachment and detachment. In general, natural fiber sheets such as paper, hydrocarbon-based plastic films such as polyethylene terephthalate (PET), polyethylene naphthalate (PEN), polyethylene (PE), polypropylene (PP), polyimide, and polyphenylene sulfide, fluorine-based films such as perfluoroalkoxyalkane (PFA), polytetrafluoroethylene (PTFE), and ethylene tetrafluoroethylene copolymer (ETFE), or materials with improved adhesion to the adherend by adding an acrylic adhesive, a urethane acrylate adhesive, a rubber adhesive, a silicone adhesive, or the like to these materials can be used. Materials with improved adhesion can support the electrolyte membrane while it is in contact with the liquid, and therefore can further prevent swelling of the electrolyte membrane.

[0100] The membrane-first catalyst layer assembly 16 supplied to the thermocompression bonding section P is subjected to a liquid application step and a thermocompression bonding step similar to those in the first embodiment, whereby the second catalyst layer is thermocompressed as a catalyst-layer-attached gas diffusion layer with the first catalyst layer covered with a cover film, to form a membrane-electrode assembly 13c.

[0101] The membrane-electrode assembly 13c that has passed through the thermocompression bonding section P is wound up in a roll by the winding roll 15. The cover film 61 may be wound up while still bonded to the membrane-electrode assembly 13c, or may be peeled off from the membrane-electrode assembly 13c by the hot press roll 40B immediately after pressing. By winding up the membrane-electrode assembly 13c while the cover film 61 is still bonded to the membrane-electrode assembly 13c, it is possible to prevent the electrolyte membrane with the catalyst layer from wrinkling or stretching, and to protect the catalyst layer from physical damage caused by external factors. In addition, by peeling off the cover film 61 immediately after thermocompression bonding to expose the catalyst layer, it is possible to effectively discharge the vapor of the liquid generated in the thermocompression bonding process. In this case, the catalyst layer can also be protected with a new cover film before winding up.

[0102] In this state, there is no gas diffusion layer on the surface of the electrolyte membrane where the first catalyst layer is formed, but it is possible to provide a function by sandwiching a frame-shaped cutout film before bonding the gas diffusion layer. Alternatively, the electrolyte membrane can be cut to the desired size without a gas diffusion layer on the surface where the first catalyst layer is formed, and then bonded to a frame-shaped film material or gas diffusion layer to form a single MEA. Furthermore, the gas diffusion layer may be laminated through a series of steps in which the electrolyte membrane is coated with a catalyst solution for forming the first catalyst layer, covered with a gas diffusion layer before drying, and the catalyst layer is dried through the gas diffusion layer.

[0103] [Third embodiment: Production of membrane-electrode assembly 3] In the third embodiment, first, a first catalyst layer-attached gas diffusion layer is formed on one side of an electrolyte membrane by a membrane-electrode assembly manufacturing apparatus 103 according to an embodiment shown in Fig. 4. The first catalyst layer-attached gas diffusion layer is formed as follows.

[0104] In this embodiment, the electrolyte membrane 10' is supplied to the catalyst layer forming apparatus 103 in a state where it is supported on a support. The electrolyte membrane 10' with the support is unwound from an electrolyte membrane supply roll 11 and supplied to a thermocompression bonding section P. The electrolyte membrane 10' supplied to the thermocompression bonding section P is subjected to a liquid application step and a thermocompression bonding step similar to those in the first embodiment, whereby the first catalyst layer-coated gas diffusion layer is thermocompression bonded to the electrolyte membrane 10' to form a membrane-first catalyst layer assembly 16'.

[0105] The membrane / first catalyst layer-attached gas diffusion layer assembly 16 ′ with the support attached is delivered by the delivery roll 14 and taken up in a roll by the take-up roll 17 .

[0106] Next, a second catalyst layer is formed on the surface of the electrolyte membrane opposite to the surface on which the first catalyst-layer-coated gas diffusion layer is formed, by a catalyst layer-forming apparatus 104 according to the embodiment shown in Fig. 5. The second catalyst layer is formed as follows.

[0107] The membrane / first catalyst layer assembly 16′ is unwound from the supply roll 18, and the support 51 is peeled off from the interface with the electrolyte membrane via guide rolls 26A and 26B. The peeled support 51 is taken up by the support take-up roll 50.

[0108] The membrane-first catalyst layer-attached gas diffusion layer assembly 16' from which the support 51 has been peeled off is subjected to a catalyst solution coating means 72 and drying means 74 similar to those in the third embodiment to form a second catalyst layer, thereby forming a membrane-electrode assembly 13d.

[0109] The membrane-electrode assembly 13d is delivered by a delivery roll 14 and taken up in a roll by a take-up roll 15.

[0110] In this state, there is no gas diffusion layer on the side of the electrolyte membrane where the second catalyst layer is formed, but it is possible to give it functionality by sandwiching a frame-shaped cutout film before bonding the gas diffusion layer. Alternatively, it is possible to cut the electrolyte membrane to the desired dimensions without a gas diffusion layer on the side where the second catalyst layer is formed, and then bond a frame-shaped film material or gas diffusion layer to create a single MEA. EXAMPLES

[0111] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples.

[0112] In Examples 1 to 6, the gas diffusion layer with a catalyst layer was prepared by coating a catalyst coating liquid consisting of a Pt-supported carbon catalyst TEC10E50E manufactured by Tanaka Kikinzoku Kogyo Co., Ltd. and a "Nafion" (registered trademark) solution on a gas diffusion layer 28BC manufactured by SGL as a substrate, and drying the catalyst layer to prepare a roll of the gas diffusion layer with a catalyst layer (substrate width 100 mm, thickness 240 μm) (platinum loading amount: 0.3 mg / cm 2 ).

[0113] The electrolyte membranes in Examples 2 to 6 were produced with reference to the production method described in JP 2018-60789 A.

[0114] [Example 1] Using an apparatus having a schematic configuration as shown in FIG. 1, the catalyst layer of the above-mentioned catalyst-layer-attached gas diffusion layer was bonded to one side of a commercially available "Nafion" (registered trademark) membrane, product name NR211 (film thickness 25 μm), used as an electrolyte membrane, according to the method described in the first embodiment.

[0115] In the liquid application process, 100% pure water was sprayed to the catalyst layer at a depth of 1 cm using a fan-shaped spray nozzle CBIMV 80005S manufactured by Ikeuchi Co., Ltd. 2 The solution was applied dropwise in an amount of 0.4 μL per drop.

[0116] In the thermocompression bonding process, a pair of heat press rolls with a diameter of 250 mm were used, one of which was a stainless steel roll and the other a fluororubber roll with a hardness of 90° (Shore A). The pressure of the heat press roll was 3.0 MPa. The pressure was measured using a press scale made by Fujifilm Corporation. The roll surface temperature was 160°C, and the heating temperature was measured using a thermocouple attached to the bonding interface, resulting in a value of 115°C. The transport speed of the electrolyte membrane and the gas diffusion layer with catalyst layer was 4.0 m / min.

[0117] Visual inspection of the resulting membrane-electrode assembly revealed that there was no damage to the catalyst-coated gas diffusion layer, and no swelling or wrinkling of the electrolyte membrane, and that the assembly was of high quality. [Example 2] Using an apparatus having a schematic configuration as shown in FIG. 1, a catalyst layer of the same catalyst layer-attached gas diffusion layer as used in Example 1 was bonded to one side of a polyether ketone-based polymer electrolyte membrane made of a polymer represented by the following formula (G1), in accordance with the method described in the first embodiment.

[0118] [ka]

[0119] In the liquid application process, 100% pure water was sprayed to the catalyst layer at a depth of 1 cm using a fan-shaped spray nozzle CBIMV 80005S manufactured by Ikeuchi Co., Ltd. 2 0.4 μL was added per well.

[0120] In the thermocompression bonding process, a pair of heat press rolls with a diameter of 250 mm were used, one of which was a stainless steel roll and the other a fluororubber roll with a hardness of 90° (Shore A). The pressure of the heat press roll was 4.8 MPa. The pressure was measured using a press scale made by Fujifilm Corporation. The temperature of the roll surface was 160°C, and the heating temperature was measured using a thermocouple attached to the bonding interface, resulting in a value of 115°C. The transport speed of the electrolyte membrane and the gas diffusion layer with catalyst layer was 4.0 m / min.

[0121] Visual inspection of the resulting membrane-electrode assembly revealed that there was no damage to the catalyst-coated gas diffusion layer, and no swelling or wrinkling of the electrolyte membrane, and that the assembly was of high quality.

[0122] [Example 3] Using an apparatus having a schematic configuration as shown in FIG. 1, the catalyst layer of the above-mentioned catalyst layer-attached gas diffusion layer was bonded to one side of a polyarylene-based polymer electrolyte membrane made of a polymer represented by the following formula (G2), according to the method described in the first embodiment.

[0123] [ka]

[0124] (In formula (G2), k, m, and n are integers, k is 25, m is 380, and n is 8.) The liquid application step and the thermocompression bonding step were carried out in the same manner as in Example 2.

[0125] Visual inspection of the resulting membrane-electrode assembly revealed that there was no damage to the catalyst-coated gas diffusion layer, and no swelling or wrinkling of the electrolyte membrane, and that the assembly was of high quality. [Example 4] Using an apparatus having a schematic configuration as shown in FIG. 1, and according to the method described in the first embodiment, the catalyst layer of the above-mentioned catalyst layer-attached gas diffusion layer was bonded to one side of a polyethersulfone-based polymer electrolyte membrane composed of a segment represented by the following formula (G3) and a segment represented by the following formula (G4).

[0126] [ka]

[0127] (In formulas (G3) and (G4), p, q, and r are integers, p is 170, q is 380, and r is 4.) The liquid application step and the thermocompression bonding step were carried out in the same manner as in Example 2.

[0128] Visual inspection of the resulting membrane-electrode assembly revealed that there was no damage to the catalyst-coated gas diffusion layer, and no swelling or wrinkling of the electrolyte membrane, and that the assembly was of high quality.

[0129] [Example 5] A membrane-electrode assembly was produced according to the method described in the second embodiment above.

[0130] Using an apparatus with a schematic configuration shown in Fig. 2, a catalyst solution was applied to one side of a polyetherketone-based polymer electrolyte membrane made of a polymer represented by the formula (G1) and dried to form a first catalyst layer. The catalyst solution used was a catalyst coating solution made of Pt-supported carbon catalyst TEC10E50E manufactured by Tanaka Kikinzoku Kogyo Co., Ltd. and a "Nafion" (registered trademark) solution. The solution was dried at 120°C for 5 minutes to obtain a catalyst layer with a layer thickness of 5 µm.

[0131] Next, using an apparatus having a schematic configuration as shown in Fig. 3, the catalyst layer of the aforementioned gas diffusion layer with catalyst layer was bonded to the other surface of the polyetherketone-based polymer electrolyte membrane on which the first catalyst layer was formed, to form a gas diffusion layer with a second catalyst layer. For the cover film to be laminated on the surface of the first catalyst layer, a PET film "Lumirror" (registered trademark) manufactured by Toray Industries, Inc. with a film thickness of 75 µm was used. The liquid application process and the thermocompression bonding process were carried out in the same manner as in Example 2.

[0132] When the cover film was peeled off from the obtained membrane-electrode assembly, no deposits were found on the cover film. In addition, visual evaluation of the obtained membrane-electrode assembly revealed no damage to the gas diffusion layer with catalyst layer, and no swelling or wrinkles in the electrolyte membrane, indicating that the assembly was of high quality.

[0133] [Example 6] A membrane-electrode assembly was produced according to the method described in the third embodiment above.

[0134] The first catalyst layer was bonded to one side of the polyetherketone-based polymer electrolyte membrane made of the polymer represented by the formula (G1) by using an apparatus having a schematic configuration shown in Fig. 4. The liquid application step and the thermocompression bonding step were performed in the same manner as in Example 2.

[0135] Next, using an apparatus having a schematic configuration as shown in FIG. 5, the same catalyst solution as in Example 5 was applied to the other side of the electrolyte membrane on which the first catalyst layer-coated gas diffusion layer was formed, and then dried to form a second catalyst layer.

[0136] Visual inspection of the resulting membrane-electrode assembly revealed that there was no damage to the catalyst-coated gas diffusion layer, and no swelling or wrinkling of the electrolyte membrane, and that the assembly was of high quality.

[0137] [Example 7] Except for using the following composite electrolyte membrane as the electrolyte membrane, a membrane-electrode assembly was produced in the same manner as in Example 1. The obtained membrane-electrode assembly was visually evaluated and found to be of high quality with no damage to the catalyst layer-attached gas diffusion layer or swelling or wrinkling of the electrolyte membrane.

[0138] <Composite electrolyte membrane> A composite electrolyte membrane made by impregnating a 6 μm thick PTFE porous substrate (Tetratex, a registered trademark of Donaldson Company) with the following fluorine-based electrolyte solution.

[0139] <Fluorine-based electrolyte solution> Eighty parts by mass of ethylene glycol was added to 100 parts by mass of a 20% solution of "Nafion (registered trademark)" in n-propanol, and the n-propanol was removed under reduced pressure to replace the solvent, thereby obtaining an ethylene glycol solution of "Nafion".

[0140] [Example 8] A membrane-electrode assembly was produced in the same manner as in Example 5, except that the following composite electrolyte membrane was used as the electrolyte membrane. The resulting membrane-electrode assembly was visually evaluated and found to be of high quality, with no damage to the catalyst layer-attached gas diffusion layer or swelling or wrinkling of the electrolyte membrane.

[0141] <Composite electrolyte membrane> A composite electrolyte membrane made by impregnating a 6 μm thick PTFE porous substrate (Tetratex, a registered trademark of Donaldson Company) with the following hydrocarbon electrolyte solution.

[0142] <Hydrocarbon-based electrolyte solution> The solution was prepared by dissolving 0.26 parts by mass of a nonionic fluorine-based surfactant (polyoxyethylene ether-based surfactant "Ftergent" (registered trademark) FTX-218 manufactured by Neos Corporation) in 100 parts by mass of an N-methylpyrrolidone (NMP) solution (electrolyte concentration: 13% by mass) in which the polyether ketone-based polymer electrolyte represented by the formula (G1) was dissolved.

[0143] [Example 9] A membrane-electrode assembly was produced in the same manner as in Example 1, except that the nozzle chambers 32A and 32B were not depressurized in the production apparatus of Fig. 1. The obtained membrane-electrode assembly was visually evaluated and found to be of high quality, with no damage to the catalyst layer-attached gas diffusion layer and no swelling or wrinkling of the electrolyte membrane.

[0144] [Comparative Example 1] A catalyst layer was bonded to one side of the electrolyte membrane in the same manner as in Example 2 using the same catalyst-layer-equipped gas diffusion layer as used in Example 1, except that the liquid application step was not performed. The obtained membrane-electrode assembly was visually evaluated, and poor adhesion between the electrolyte membrane and the catalyst layer was found. [Industrial Applicability]

[0145] The membrane-electrode assembly of the present invention can be applied to, for example, solid polymer fuel cells, solid polymer electrolyte membrane water electrolysis devices, electrochemical hydrogen pumps, and the like. [Explanation of symbols]

[0146] 100, 102, 103: Membrane-electrode assembly manufacturing equipment 101, 104: Catalyst layer forming device 10, 10': Electrolyte membrane 11, 18: Electrolyte membrane supply roll 13a, 13b, 13c, 13d: Membrane-electrode assembly 14: Delivery roll 15, 17: Winding roll 16: Membrane-first catalyst layer assembly 16': Membrane-first catalyst layer-gas diffusion layer assembly 12, 22A, 22B, 26A, 26B, 27A, 27B: Guide rolls 20A, 20B: Gas diffusion layer with catalyst layer 21A, 21B: catalyst layer-attached gas diffusion layer supply roll 30A, 30B: Spray nozzle 31A, 31B, 73: Backup roll 32A, 32B: Nozzle chamber 33A, 33B: Valve 34A, 34B: Pressure reducing tank 40A, 40B: Heat press roll 41A, 41B: Heat shield 50: Support winding roll 51:Support 60: Cover film supply roll 70: Catalyst solution tank 71: Catalyst solution delivery pump 72: Application means 74:Drying means P:Thermocompression bonding part S: Space

Claims

1. A method for producing a membrane electrode assembly in which a catalyst layer-equipped gas diffusion layer is joined to an electrolyte membrane, comprising the steps of: a liquid applying step of applying a liquid under an air atmosphere only to the surface of the catalyst layer before bonding; a thermocompression bonding step of bonding the electrolyte membrane and the gas diffusion layer with the catalyst layer to which the liquid has been applied by thermocompression bonding; wherein the liquid applied in the liquid application step is a liquid containing water.

2. 2. The method for producing a membrane-electrode assembly according to claim 1, wherein the water content in the water-containing liquid is 50% by mass or more and 100% by mass or less.

3. 3. The method for producing a membrane-electrode assembly according to claim 2, wherein the liquid applied in the liquid application step is pure water.

4. 4. The method for producing a membrane-electrode assembly according to claim 1, wherein in the liquid applying step, the liquid is applied in the form of droplets onto the surface of the catalyst layer of the catalyst-layer-attached gas diffusion layer.

5. The method for producing a membrane-electrode assembly according to claim 4 , wherein in the liquid applying step, the liquid is applied by spraying.

6. In the liquid application step, the amount of the liquid in the thermocompression bonding step is set to 1 cm over the surface of the catalyst layer. 2 The method for producing a membrane-electrode assembly according to any one of claims 1 to 5, wherein the amount of the solution per unit area is 0.1 µL or more and 5 µL or less.

7. 7. The method for producing a membrane-electrode assembly according to claim 1, wherein the electrolyte membrane is a hydrocarbon-based electrolyte membrane.

8. A method for producing a membrane-electrode assembly, comprising bonding a catalyst-layer-equipped gas diffusion layer to a surface of the electrolyte membrane by the method according to any one of claims 1 to 7.

9. A step of applying a catalyst solution to one surface of the electrolyte membrane and drying the solution to form a first catalyst layer; bonding a second catalyst layer-coated gas diffusion layer to the other surface of the electrolyte membrane; having the step of bonding the second catalyst layer-coated gas diffusion layer includes a liquid application step of applying a liquid only to the surface of the second catalyst layer before bonding in an atmospheric environment; a thermocompression bonding step of bonding the second catalyst layer-attached gas diffusion layer to which the liquid has been applied and the electrolyte membrane by thermocompression bonding; The present invention relates to a method for producing a membrane electrode assembly having the above structure.

10. 10. The method for producing a membrane-electrode assembly according to claim 9, further comprising the step of covering the first catalyst layer with a cover film, and the step of joining the second catalyst layer-coated gas diffusion layer is performed in a state where the first catalyst layer is covered with the cover film.

11. The step of forming the first catalyst layer comprises: covering the first catalyst layer with a gas diffusion layer before drying; drying the first catalyst layer through the gas diffusion layer; The method for producing a membrane-electrode assembly according to claim 9 , comprising:

12. a step of bonding a first catalyst layer-coated gas diffusion layer to one surface of the electrolyte membrane; applying a catalyst solution to the other surface of the electrolyte membrane and drying the solution to form a second catalyst layer; having The step of bonding the first catalyst layer-coated gas diffusion layer includes a liquid application step of applying a liquid only to the surface of the first catalyst layer before bonding in an atmospheric environment; a thermocompression bonding step of bonding the first catalyst layer-attached gas diffusion layer to which the liquid has been applied and the electrolyte membrane by thermocompression bonding; The present invention relates to a method for producing a membrane electrode assembly having the above structure.

13. An apparatus for manufacturing a membrane electrode assembly in which a catalyst layer-equipped gas diffusion layer is bonded to an electrolyte membrane, comprising: A liquid applying means for applying a liquid to a surface of the catalyst layer before bonding; a thermocompression bonding means for bonding the catalyst layer-attached gas diffusion layer and the electrolyte membrane by thermocompression bonding while transporting each of them; wherein the liquid applied by the liquid applying means is a liquid containing water.

14. 14. The apparatus for producing a membrane electrode assembly according to claim 13, wherein the liquid supplying means supplies the liquid in the form of droplets onto the surface of the catalyst layer.

15. The apparatus for producing a membrane-electrode assembly according to claim 14, wherein the liquid applying means is a spray.

Citation Information

Patent Citations

  • Manufacturing method for electrolytic membrane -electrode substrate complex

    JP2004253267A

  • Manufacturing method of junction of electrolyte membrane and electrode

    JP2005158518A

  • Manufacturing method of membrane electrode junction

    JP2005222894A

  • Membrane-electrode assembly manufacturing method

    JP2009140652A

  • Manufacturing method of membrane electrode assembly for polymer electrolyte fuel cell

    JP2013069535A